2019
DOI: 10.2147/cmar.s211372
|View full text |Cite
|
Sign up to set email alerts
|

<p>F factor plasmid-mediated Epstein-Barr virus genome introduction establishes an EBV positive NPC cell model</p>

Abstract: Background Most Epstein-Barr virus (EBV)-positive cells lose the EBV episomes upon prolonged propagation. Purpose The purposes of this study were to establish a simple cell model for nasopharyngeal carcinoma (NPC) research by introducing a plasmid with the EBV genome into NPC cells and then to investigate the resulting changes in malignant biological behaviour and NPC-associated signalling pathways. Methods HONE1 NPC cells were transfected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The PI3K/Akt pathway is vital to NPC progression, metastasis, and invasion [54]. After the EBV genome is introduced into the NPC cells, this pathway could be activated [55]. A study showed that inhibiting the PI3K/Akt pathway could suppress NPC cell metastasis by inducing mesenchymal-epithelial reverting transition [56].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway is vital to NPC progression, metastasis, and invasion [54]. After the EBV genome is introduced into the NPC cells, this pathway could be activated [55]. A study showed that inhibiting the PI3K/Akt pathway could suppress NPC cell metastasis by inducing mesenchymal-epithelial reverting transition [56].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway is vital to NPC progression, metastasis, and invasion [52]. After the EBV genome is introduced into the NPC cells, this pathway could be activated [53]. A study showed that inhibiting the PI3K/Akt pathway could suppress NPC cell metastasis by inducing mesenchymal-epithelial reverting transition [54].…”
Section: Discussionmentioning
confidence: 99%
“…The JAK/STAT signaling pathway was significantly inhibited, whereas the NF-κB and PI3K/AKT signaling pathways were enhanced in HONE1 cells. The direct effect on cells can be illustrated by enhanced cell proliferation and migration, accelerated cell cycle progression, and inhibited cell apoptosis [ 72 ]. A comprehensive examination of various signaling pathways could be helpful for making correct decisions regarding treatment.…”
Section: Six Main Signaling Pathways Of Ebv-associated Neoplasmsmentioning
confidence: 99%